Molecular docking based virtual screening of compounds for inhibiting sortase A in L.monocytogenes - Rashidieh, Behnam (Bioinformation, 2015)
Listeriosis is considered as an important public health issue. Sortase A (srtA) is an enzyme with catalytic role in L. monocytogenes that breaks the junction between threonine and glycine in the LPXTG motif (a key motif in internalin A (InlA) that plays an important role in listeriosis). Inactivation of srtA was shown to inhibit anchoring of the invasion protein InIA. This is in addition to inhibiting peptidoglycan-associated LPXTG proteins. Therefore, it is of interest to inhibit strA using potential molecules. Here, we describe the design of an inhibitor with high binding affinity to srtA with the ability to prevent the attachment of srtA to the LPXTG proteins such as InIJ. A homology model of Listeria monocytogenes Sortase A was developed using MODELLER (version 9.12). We screened StrA to 100,000 drug-like ligands from the Zinc database using Molecular docking and virtual screening tool PyRX). Pharmacokinetic analysis using the FAFDrugs(3) web server along with ADME and toxicity analysis based on Lipinski rule of five were adopted for the screening exercise followed by oral toxicity check using PROTOX (a server) for every 10 successive hits. The results from PROTOX server indicated that Lig #1 (with LD50 of 2000mg/kg) and Lig #7 (with LD50 of 2000mg/kg) have toxicity class 4 and Lig #3 (with LD50 of 14430mg/kg) has toxicity class 6. Subsequent modifications of these structures followed by FAFDrugs(3) analysis for high bioavailability value selected Lig #7 according to Lipinski rules of five. Thus, Lig #7 with IUPAC name ((R)-4-{(S)-1-[(S)-2-Amino-4-methylvaleryl]-2-pyrrolidinyl}-1-[(S)-1-(ethylamino) carbonyl-propylamino] -2-propyl-1, 4- butanedione) is suggested as a potential candidate for srtA inhibition for further consideration.